The Riddle of the Extra Bushels! - Dow Chemical Company (1951)
Black and white print advertisement for a range of agricultural chemicals manufactured and sold by the Dow Chemical Company, including weed killers, insecticides, fungicides, plant growth regulators, and grain and soil fumigants. The advertisement features an illustration of corn stalks and bushels, with accompanying text detailing how the use of Dow products leads to better crop yields. This advertisement appeared on page 81 of the June 1951 edition of Country Gentleman.
Keywords: Dow Chemical Company; Insecticides; Agricultural chemicals; Agricultural chemicals industry; Fungicides; Herbicides; Advertising; Advertising, Industrial; Chemical industry; Corporations